Transformation of the Spread of the Manunggaling Kawula lan Gusti Concept in Javanese Society from the 16th Century AD to the 21st Century AD - Dwi Afrianti (International Journal of Islamic Khazanah, 2019)
The Manunggaling Kawula lan Gusti concept was found in Serat Nawa Ruci in the Middle Ages of Java in the 16th Century AD and was re-transformed into the New Javanese era in Dewa Ruci Fiber, Cabolek Fiber, Malaya Syeh Fiber until the 20th century AD in Fiber Sastra Jendra (Literature Aji Endra) which is still used today. Over five centuries, the concept experienced distortion of meaning far from the purpose and purpose of its writing. This study was analyzed using the theoretical basis of the R. G. Collingwood Historical Philosophy aimed to find out the development of Sufism in Java, the transformation of the spread of the concept in several Islamic Javanese texts derived from the Nawa Ruci Fiber, and its interpretation in the Fiber of Jendra's Literature. using historical research methods with heuristic steps, criticism, interpretation, and historiography. The manuscripts used obtained from utilizing manuscripts as a result of philological research or translation that have never been studied by others. This research found that in Indonesia, Sufi propagators of Islam in Java preached by combining local traditions with Islam, which led to the birth of Javanese Sufism.